Validity, reliability and minimal detectable change of the balance evaluation systems test (BESTest), mini-BESTest and brief-BESTest in patients with end-stage renal disease - Jácome, Cristina (2017)
PURPOSE: This study determined the validity, test-retest reliability and minimal detectable change of the balance evaluation systems test (BESTest), mini-balance evaluation systems test (Mini-BESTest) and brief-balance evaluation systems test (Brief-BESTest) in patients with end-stage renal disease. METHODS: A cross-sectional study with 74 patients with end-stage renal disease (male 66.2%; 63.9 ± 15.1 years old) was conducted. Participants were asked to report the number of falls during the previous 12 months and to complete the activity-specific balance confidence (ABC) scale. The BESTest was administered, and the Mini-BESTest and Brief-BESTest scores were computed based on the BESTest performance. Validity was assessed by correlating balance tests with each other and with the ABC scale. Test-retest relative reliability and agreement were explored with the intraclass correlation coefficient (ICC) equation (2,1) and the Bland and Altman method. Minimal detectable changes at the 95% confidence level were established. RESULTS: Balance test scores were significantly correlated with each other (spearman's correlation = 0.89-0.92) and with the ABC scale (spearman's correlation = 0.49-0.59). Balance tests presented high test-retest reliability (ICC = 0.84-0.94), with no evidence of bias. Minimal detectable change values were 10.8 (expressed as a percentage 13.5%), 5.3 (23.7%) and 5.6 (34%) points for the BESTest, Mini-BESTest and Brief-BESTest, respectively. CONCLUSIONS: All tests are valid and reliable to assess balance in patients with end-stage renal disease. Nevertheless, based on the minimal detectable changes found, BESTest and Mini-BESTest may be the most recommended tests for this specific population. Implications for Rehabilitation Balance evaluation systems test (BESTest), mini-balance evaluation systems test (Mini-BESTest) and brief-balance evaluation systems test (Brief-BESTest) are reliable and valid in patients with end stage renal disease (ESRD). The minimal detectable changes of 10.8 for the BESTest, 5.3 for the Mini-BESTest and 5.6 for the Brief-BESTest can be used by clinicians to identify a true change in balance over time or in response to interventions. Based on the minimal detectable changes found, BESTest and Mini-BESTest may be the most recommended; and the selection of one of them may be based on time and equipment availability.